The Role of Parents to Prevent Teenagers Early Marriage in Banyumas Regency, Indonesia - sistiarani, colti; hariyadi, bambang; wahyuningsih, eri; Maryati, Leni (Insights in Public Health Journal, 2023)
Early marriage is still a concrete problem. One of the factors related to preventing early marriage is the importance of emphasizing the involvement of parents in providing assistance and supervision control. This research uses a qualitative approach with a case study approach. The research location is in Datar Village, Contributing District. The research subjects in this study were the midwives of the puskesmas, village head, parents of teenagers, as well as representatives of Babinsa and the Police of the Contributing District sector with a total of 8 peoples. How to collect data by using focus group discussions. Data analysis used descriptive analysis. Prevention of early marriage requires the involvement of the role of parents through the emphasis on assistance adolescents by parents. The emphasis on assistance is carried out by building a trusting relationship between parents and adolescents, controlling adolescent behavior by parents, and participating in teenagers family development.